Effect Locus Control, Auditor Experience, Time Budget Pressure, Task Complexity, and Audit Risk On Professional Auditor Skepticism With Ethics Moderation - Alfanita Gratia Telaumbanua; Erlina Erlina; Ibnu Austrindanney Sina Azhar (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the effect of Locus of control, auditor experience, time budget pressure, task complexity, and audit risk on auditors’ professional skepticism, with ethics as a moderating variable. The research was conducted on auditors at the Inspectorate Office of Gunungsitoli City Government. This study was motivated by the low level of professional skepticism among internal government auditors, which weakens fraud detection and decreases public trust in audit results. This research employed a quantitative approach with a survey method. Primary data were collected through questionnaires distributed to auditors at the Gunungsitoli City Inspectorate. Data were analyzed using multiple linear regression and Moderated Regression Analysis (MRA) to examine the moderating effect of ethics. Validity, reliability, and classical assumption tests were conducted to ensure data quality and model feasibility. The results show that Locus of control, auditor experience, and audit risk have a positive and significant effect on professional skepticism, while time budget pressure and task complexity have a negative and significant effect. Ethics significantly moderates the relationship between all independent variables and auditors’ professional skepticism by strengthening positive influences and weakening negative ones. These findings highlight the importance of professional ethics in maintaining auditors’ skeptical, objective, and independent attitudes. Therefore, enhancing ethical integrity and auditor competence is expected to improve audit quality and increase public confidence in the financial audit results of local governments.